(3cJGH GdfjI hGdUOb hGdENdGUs
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf hfDef GjeGf GdehbJjf CeG HYO abO GdcTa dCQHGH GdbdhH HHUjQI GdGjeGf s
(3BNQgG (B:s
(3aEPG ef YdGeGJ GdUOb cJeGf GdeUGFH hGdWGYGJ hcQGgI GWdGY GdNdb YdjgG hGdSdGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(4 / 433) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs